Urban house prices and business establishment in Malaysia: a sectoral approach - Gholipour, Hassan F.; Khin, Sabai; Tan-Kantor, Angela; Spong, Heath (International Journal of Strategic Property Management, 2021)
The purpose of this study is to examine the long-run and short-run relationship between house prices and business formation in various industries. Using data from Malaysian states over the period of 2000–2016 and applying ARDL/PMG models, our results show that changes in house prices have a positive and significant association with business establishment in specific economic sectors, including manufacturing, wholesale and retail trade, information and communication, and financial and insurance in the long-run. However, the long-run relationship between house prices and business formation is negative and significant for electricity, gas, steam and air conditioning supply, construction, transportation and storage, accommodation and food service activities, and real estate industries. The short-run analysis indicates that there is a difference in the responses of business establishment in various industries to the changes in house prices.